Genome-wide association study identifies TH1 pathway genes associated with lung function in asthmatic patients - Li, Xingnan; Hawkins, Gregory A.; Ampleford, Elizabeth J.; Moore, Wendy C.; Li, Huashi; Hastie, Annette T.; Howard, Timothy D.; Boushey, Homer A.; Busse, William W.; Calhoun, William J.; Castro, Mario; Erzurum, Serpil C.; et al. (Journal of allergy and clinical immunology, 2013)
Recent meta-analyses of genome-wide association studies in general populations of European descent have identified 28 loci for lung function. We sought to identify novel lung function loci specifically for asthma and to confirm lung function loci identified in general populations. Genome-wide association studies of lung function (percent predicted FEV1 [ppFEV1], percent predicted forced vital capacity, and FEV1/forced vital capacity ratio) were performed in 4 white populations of European descent (n = 1544), followed by meta-analyses. Seven of 28 previously identified lung function loci (HHIP, FAM13A, THSD4, GSTCD, NOTCH4-AGER, RARB, and ZNF323) identified in general populations were confirmed at single nucleotide polymorphism (SNP) levels (P < .05). Four of 32 loci (IL12A, IL12RB1, STAT4, and IRF2) associated with ppFEV1 (P < 10−4) belong to the TH1 or IL-12 cytokine family pathway. By using a linear additive model, these 4 TH1 pathway SNPs cumulatively explained 2.9% to 7.8% of the variance in ppFEV1 values in 4 populations (P = 3 × 10−11). Genetic scores of these 4 SNPs were associated with ppFEV1 values (P = 2 × 10−7) and the American Thoracic Society severe asthma classification (P = .005) in the Severe Asthma Research Program population. TH2 pathway genes (IL13, TSLP, IL33, and IL1RL1) conferring asthma susceptibility were not associated with lung function. Genes involved in airway structure/remodeling are associated with lung function in both general populations and asthmatic subjects. TH1 pathway genes involved in anti-virus/bacterial infection and inflammation modify lung function in asthmatic subjects. Genes associated with lung function that might affect asthma severity are distinct from those genes associated with asthma susceptibility.